Nilai-Nilai Pernikahan Ideal Perspektif Hadis dalam Film Twivortiare - Awaliyah, Robiah (Jurnal Riset Agama, 2022)
Building an ideal marriage is an issue that often occurs in society. This study aims to discuss the ideal marriage in the film Twivortiare from a hadith perspective. This research is a qualitative type using successive thematic, takhrij and syarah approaches and the living sunnah method is used to find the ideal marriage values in the Twivortiare film. The results and discussion in this article show that in the Twivortiare film there are ideal marriage values from a hadith perspective such as treating spouses well as contained in Musnad Ahmad Number 7095, accepting and complementing each other as contained in Sahih Muslim Number 2672, and maintaining intimacy. with a partner as exemplified by Rasulullah in Sahih Bukhari Number 288. This study concludes that in the Twivortiare film there are ideal marriage values that can be a solution so that marriages avoid actions that lead to disharmony and divorce. This study recommends that every married couple can instill the value of an ideal marriage even though it is through the meaning of the film.Â